2022
DOI: 10.24272/j.issn.2095-8137.2021.252
|View full text |Cite
|
Sign up to set email alerts
|

A new species of <i>Occidozyga</i> Kuhl and van Hasselt, 1822 (Anura: Dicroglossidae) from Southern Guangxi, China

Abstract: A: Dorsal view; B: Lateral view; C: Ventral view; D: Ventral view of foot; E: Ventral view of hand; F: Various individuals showing broad pale-yellow stripe from tip of snout to vent; G: Various individuals showing broad pale yellow transverse stripe on posterior of eyes; H: Maximum-likelihood (ML) and Bayesian inference (BI) trees based on mitochondrial 12S and 16S rRNA gene fragments. Node supports are indicated on branches as ML support and Bayesian posterior probabilities. Photos by Wei-Cai Chen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…2 ). The results indicated that the monophyly of Occidozyga was strongly supported and in agreement with results of Chen et al (2022) . The specimen collected from Bac Giang Province of Vietnam, clustered with the specimens (including type specimens) of O.…”
Section: Data Resourcessupporting
confidence: 84%
See 4 more Smart Citations
“…2 ). The results indicated that the monophyly of Occidozyga was strongly supported and in agreement with results of Chen et al (2022) . The specimen collected from Bac Giang Province of Vietnam, clustered with the specimens (including type specimens) of O.…”
Section: Data Resourcessupporting
confidence: 84%
“…material 4 . Morphological characters of the specimens from Bac Giang Province agreed well with the original description of Chen et al (2022) . Size medium (SVL 28.1 mm in males, SVL 36.2–39.5 mm in females); head wider than long (HL/HW 0.86 in males, HL/HW 0.86–0.91 in females); snout round in dorsal and lateral views, projecting slightly over lower jaw; canthus rostralis broadly round; loreal region vertical and slightly concave; snout slightly shorter than eye diameter (ED/RL 1.06 in males, ED/RL 1.04–1.10 in females); internarial distance wider than interorbital distance and upper eyelid width (IND 2.7 mm, IOD 1.8 mm, UEW 2.5 mm in males; IND 2.9–3.6 mm, IOD 2.0–2.4 mm, UEW 2.3–2.8 mm in females); tympanum hidden; vomerine teeth absent; tongue fleshy, round posteriorly.…”
Section: Taxon Treatmentssupporting
confidence: 76%
See 3 more Smart Citations